2006
DOI: 10.1002/bjs.5493
|View full text |Cite
|
Sign up to set email alerts
|

Combined multichannel intraluminal impedance–pH monitoring to select patients with persistent gastro-oesophageal reflux for laparoscopic Nissen fundoplication

Abstract: Patients with a positive symptom index resistant to PPIs with non-acid or acid reflux demonstrated by MII-pH monitoring can be treated successfully by laparoscopic Nissen fundoplication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
2
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(150 citation statements)
references
References 21 publications
(13 reference statements)
3
139
2
6
Order By: Relevance
“…Small uncontrolled studies have demonstrated a benefi t for baclofen when used for refractory duodeno-gastro-esophageal refl ux in patients with persistent symptoms on PPI therapy ( 81 ). A small observational study with limited follow-up suggested a positive symptom response to surgery in this group, but improvement in refl ux control was not objectively documented ( 161 ). A more recent prospective, uncontrolled study found that 3 months aft er fundoplication, both the number of refl ux episodes and typical symptoms of GERD (heartburn and regurgitation) improved in patients who were PPI-nonresponders ( 162 ).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…Small uncontrolled studies have demonstrated a benefi t for baclofen when used for refractory duodeno-gastro-esophageal refl ux in patients with persistent symptoms on PPI therapy ( 81 ). A small observational study with limited follow-up suggested a positive symptom response to surgery in this group, but improvement in refl ux control was not objectively documented ( 161 ). A more recent prospective, uncontrolled study found that 3 months aft er fundoplication, both the number of refl ux episodes and typical symptoms of GERD (heartburn and regurgitation) improved in patients who were PPI-nonresponders ( 162 ).…”
Section: Summary Of the Evidencementioning
confidence: 99%
“…This observation is very important because aspiration of nonacid reflux can also cause respiratory symptoms. For instance, Mainie et al (13) were able to identify by pH impedance monitoring patients with cough due to nonacid reflux while treated by proton pump inhibitors. A laparoscopic Nissen fundoplication improved or resolved the symptoms in 13 of 14 such patients (93%).…”
Section: Is Surgical Treatment Effective and Does It Alter The Naturamentioning
confidence: 99%
“…It has been reported that patients with a positive symptom index and SAP who are not responsive to PPI therapy, but demonstrate evidence of persistent non-acid or acid reflux using MII-pH monitoring can be treated successfully with laparoscopic Nissen fundoplication. 35 Surgical anti-reflux management can provide reflux control for carefully selected reflux hypersensitivity patients. 9 Similarly, Broeders et al 36 reported that laparoscopic Nissen fundoplication drastically reduced the incidence of acid and weakly acidic reflux, as well as liquid and mixed reflux episodes.…”
Section: Treatmentmentioning
confidence: 99%